Hubungan Lama Pemberian Susu Formula Dengan Tingkat Kejadian Karies Gigi Anak Usia Prasekolah TK Aisyiyah 2 Pangkajene - Arsyad; Kassaming; Nurhamzah (Jurusan Keperawatan Gigi Poltekkes Kemenkes Makassar, 2023)
Dental caries is a disease of tooth tissue with damage that starts from the surface of the enamel, dentin, then extends towards the pulp. One of the factors causing dental caries in children is formula feeding for a long time. Formula milk is formulated to resemble mother's milk (ASI), given to infants and children as a substitute for breast milk. Formula milk contains sucrose which is capable of being fermented by bacteria so that it can cause dental caries in children. The purpose of this study was to determine the relationship between duration of formula feeding and the incidence of preschool dental caries in Aisyiyah 2 Pangkajene Kindergarten. This research is a quantitative study using an analytic survey design with a cross sectional study approach. The sample in this study was Aisyiyah 2 Pangkajene Kindergarten students and the sampling technique used was a total sampling of 35 students. From the results of the chi square test, p = 0.02 which indicates a p value <0.05 so it can be concluded that there is a relationship between duration of formula feeding and the incidence of dental caries in preschool-aged children in Aisyiyah Kindergarten. Keywords: Formula milk; dental caries; preschool age